Gathering Ecofeminist Stories with Kateryna Hrushevs'ka - Zamuruieva, Iryna (East/West, 2024)
In this essay, I offer a critical ecofeminist reading of Ukrainian ethnographer and sociologist Kateryna Hrushevs'ka (1900–43). I argue that her work, understood in the wider context of feminist and ecological struggles, generates valuable insights on the intersections of environmental and gender oppressions in Ukraine. I adapt the conceptual lens of gathering to draw attention to the political commitments that become possible once the (eco)feminist political agenda is carefully gathered and analyzed in relation to its consequences for the environmental humanities field.